Water-splitting manganese complex controls light-induced redox changes of cytochrome b559 in photosystem II - Sinha, Rakesh Kumar; Tiwari, Arjun; Pospísil, Pavel (Journal of bioenergetics and biomembranes, 2010)
The effect of water-splitting Mn complex on light-induced redox changes of cytochrome b(559) (cyt b(559)) was studied in spinach photosystem II (PSII) membranes. Photoreduction of the heme iron in the intact PSII membranes was completely suppressed by DCMU, whereas photoreduction and photooxidation of the heme iron in the Mn-depleted PSII membranes were unaffected by DCMU. Interestingly, photoreduction and photooxidation of the heme iron in the Mn-depleted PSII membranes were completely diminished by exogenous superoxide dismutase (SOD), whereas no effect of SOD on photoreduction of the heme iron was observed in the intact PSII membranes. The current work shows that the light-induced redox changes of cyt b(559) proceed via a different mechanism in the both types of PSII membranes. In the intact PSII membranes, photoreduction of the heme iron is mediated by plastoquinol. However, in the Mn-depleted PSII membranes, photoreduction and photooxidation of the heme iron are mediated by superoxide anion radical formed in PSII.
Keywords: cytochromy typu b; rostlinné proteiny; fotosystém II (proteinový komplex); konformace proteinů; Manganese; voda; Plant Proteins; oxidace-redukce; Water; Protein Conformation; Oxidation-Reduction; Photosystem II Protein Complex; mangan; Spinacia oleracea; Cytochrome b Group